The broad spectrum of clinical manifestations observed in three patients with L2 hydroxyglutaric aciduria spans from febrile seizures to complex dystonia - A. Alsayed; M. Albadrani; A. Obaid; A. Alhashim; A. Alakkas (Molecular Genetics and Metabolism Reports, 2024)
L-2 hydroxyglutaric aciduria (L-2-HGA) is a rare autosomal recessive progressive, organic aciduria which presents with a wide variety of clinical manifestations. Diagnosis is complex and necessitates an increase in clinical suspicion of the disease to obtain the necessary diagnostic tests and thus early administration of appropriate management.In this case series, we are reporting three cases of patients with L-2-HGA who presented with a variety of clinical manifestations. All patients presented with a constellation of symptoms including febrile seizures, hyperactivity and intellectual difficulties. One case had an unusual presentation of cervical dystonia in early adulthood. Another case had a homozygous variant, L2HGDH: NM_024884.3: c.368 A > G p. (Tyr123Cys) classified as variant of uncertain significance (VUS) at that time but recently has been reclassified as likely pathogenic variant in clin var. Furthermore, brain MRI of two patients depicted characteristic signs consistent with L-2-HGA. The findings include, symmetrical confluent high T2/FLAIR signal intensity of the white matter involving the subcortical U fibers and deep white matter with sparing of the immediate periventricular white matter, internal capsules and corpus callosum. There was also symmetric abnormal T2 signal intensity of the caudate nuclei, lentiform nucleus as well as the dentate nuclei of the cerebellum.Overall, only few cases with similar genetic mutation have been documented in the literature and were of Saudi origin. The aim of the study is to highlight the clinico-radiological features of L-2-HGA to aid in early, prompt diagnosis, and thus appropriate follow up and management of the disease with riboflavin, levocarnitine and a low-lysine diet.